Pregnancy in Non-Communicating Unicornuate Uterus: Diagnosis Difficulty and Outcomes – a Case Report - Souza, Camila Silveira de; Dorneles, Gabriela Gindri; Mendonça, Giana Nunes; Santos, Caroline Mombaque dos; Gallarreta, Francisco Maximiliano Pancich; Konopka, Cristine Kolling (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Approximately 1 in every 76,000 pregnancies develops within a unicornuate uterus with a rudimentary horn. Müllerian uterus anomalies are often asymptomatic, thus, the diagnosis is a challenge, and it is usually made during the gestation or due to its complications, such as uterine rupture, pregnancy-induced hypertension, antepartum, postpartum bleeding and intrauterine growth restriction (IUGR). In order to avoid unnecessary cesarean sections and the risks they involve, the physicians should consider the several approaches and for how long it is feasible to perform labor induction in suspected cases of pregnancy in a unicornuate uterus with a rudimentary horn, despite the rarity of the anomaly. This report describes a case of a unicornuate uterus in which a pregnancy developed in the non-communicating rudimentary horn and the consequences of the delayed diagnosis.
Keywords: uterus; abnormalities; pregnancy; parturition; pregnancy complications